MODELS OF THE MIGRATION PROCESS OF FORMATION OF DRAINAGE WATER MINERALIZATION - Khudaykulov S. I.; Abdullaev B. Kh.; Odiljonov O. M.; О. G‘. G‘ulomov; B. S. Tuxliyev; G‘. Оmonov; Xalilov Saidakbar Muratovich, N. Xalilov; N. Saidova (Web of Journals Publishing, 2025)
The article presents a calculation scheme of meliorative drainage with an uneven field of filtration rates in the cover layer. Various intensities of settlement and the influence on the formation of mineralization of drainage waters are studied. Theoretical and experimental studies of the field of filtration rates during desalination of gray soils of the arid zone, part of the Fergana Valley zone, where 3 zones with a characteristic range of filtration rates can be distinguished in the cover layer, are analyzed. The boundaries of the filtration rate zones are given.